Comparison of the corrosion behavior of AISI 304, AISI 316L and duplex steel in chloride solution - Senka Gudić; Ladislav Vrsalović; Mirko Gojić (Zaštita Materijala)
The corrosion behavior of stainless steels (AISI 304, AISI 316L and duplex steel) in NaCl solution was investigated using open circuit potential measurements, cyclic polarization and linear sweep voltammetry measurements. After cyclic polarization measurements electrode surfaces was investigated by light microscope. Duplex steel have the most noble open circuit potential, the lowest corrosion current density and the largest width of the passive region indicates its highest corrosion resistance. Also, compared to other samples, duplex steel shows the possibility of self-healing of oxide film. Increasing the concentration of Cl- ion, the depassivation potential becomes more negative for all investigated samples. If the potential scan rate increases depassivation potential becomes more positive, meaning that a certain time (induction time) is needed for the pitting occurs after the actual depassivation potential is established. Depassivation potential and pitting corrosion nucleation time of investigated samples increase in order: AISI 304 < AISI 316L < duplex steel. Light microscopy investigations of samples reveal pits on the surface of AISI 304 and AISI 316L steel while duplex steel surface is almost clear of any corrosion damage.